Prevalence and clinical features of multiple sclerosis in Latin America (2013)
Multiple sclerosis (MS) in Latin America (LA) is considered to have a low to medium prevalence. However, accurate information on MS in LA is scarce. The aim of this study was to compare clinical characteristics among LA patients through a systematic review of the literature. A systematic search (Spanish, Portuguese and English) was done for all clinical studies of MS in humans (MEDLINE, PubMed, Scielo, BIREME, EMBASE and LILACS) up to May 2011 being focused on a well-defined Latin American population (peer-reviewed journal) following the MOOSE guidelines. The search strategy included combinations of different Mesh terms (two independent researchers). Classification of each article by using the Oxford Centre for Evidence-based Medicine-Levels of Evidence was done. The total number of patients per country for each specific characteristic was compiled. Chi-square test was used to compare the characteristics in the studies retrieved per country. There were 38 articles fulfilling the inclusion criteria, accounting for 4524 patients. Relapsing-remitting form was the most frequent in LA patients and the main initial symptom was motor, followed by optic neuritis and sensorial. A mild expanded disability status scale was the most prevalent in all LA countries. Factors accounting for differences in distribution and clinical course across LA countries include genetics, environment, diagnostic techniques, socioeconomic structure and medical facilities. © 2012 Elsevier B.V.